2005
DOI: 10.1158/0008-5472.can-04-3119
|View full text |Cite
|
Sign up to set email alerts
|

Versatile Prostate Cancer Treatment with Inducible Caspase and Interleukin-12

Abstract: To establish optimized conditions for immunity against prostate cancer, we compared the efficacy of multiple approaches in autochthonous and s.c. transgenic adenocarcinoma of the mouse prostate (TRAMP)-based models. Mice immunized with interleukin (IL)-12-containing apoptotic, but not necrotic TRAMP-C2 cell-based, vaccines were resistant to TRAMP-C2 tumor challenge and re-challenge, independently of the route of vaccination (s.c. or i.p.). Administration of ;-irradiated TRAMP-C2 cells preinfected with adenovir… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
7
0

Year Published

2006
2006
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 55 publications
(59 reference statements)
0
7
0
Order By: Relevance
“…IL-12 is an important factor in regulation of innate and adaptive immunity [20]. Tarrant et al reported that increased serum IL-12 could promote the production of IFN-γ and nitric oxide, and further enhance the inflammatory response of autoimmune uveitis [21].…”
Section: Discussionmentioning
confidence: 99%
“…IL-12 is an important factor in regulation of innate and adaptive immunity [20]. Tarrant et al reported that increased serum IL-12 could promote the production of IFN-γ and nitric oxide, and further enhance the inflammatory response of autoimmune uveitis [21].…”
Section: Discussionmentioning
confidence: 99%
“…To date, this is the first efficacious treatment for TRAMP mice at an advanced stage of disease (29,30,(33)(34)(35) and the only report of the cure of spontaneous tumors with unmanipulated, unselected donor T lymphocytes. These findings are of particular relevance in the TRAMP model in which the genetic pressure for cancer recurrence is particularly strong (11) and able to induce unresponsiveness of high-affinity tumor-specific T cells (36,37).…”
Section: Discussionmentioning
confidence: 99%
“…Identification of inflammasome-independent mechanisms of caspase-1 activation would help resolve the function of caspase-1 in prostate cancer. Adenoviruses expressing inducible caspase-1 have been used to treat prostate tumors in mouse models in combination with other molecules [21]. However, the molecular mechanisms of caspase-1-induced apoptosis have not been well characterized.…”
Section: The Role Of Inflammasome Components and Regulators In Prostamentioning
confidence: 99%